Control of clethodim-resistant Lolium rigidum (rigid ryegrass) in triazine-tolerant canola (Brassica napus L.) in southern Australia. (December 2015) - Saini, Rupinder Kaur; Kleemann, Samuel G.L.; Preston, Christopher; Gill, Gurjeet S.
Abstract: Two field experiments were conducted during 2013 and 2014 at Roseworthy, South Australia, to identify effective herbicide options for the control of clethodim-resistant Lolium rigidum in triazine-tolerant canola. Dose response experiments in pots confirmed resistance in both field populations (F4-2013 and S2-2014) of L. rigidum to clethodim and butroxydim. At the recommended field rate of clethodim (120 g ha −1 ), F4 and S2 populations had 45% and 67% survival, respectively. Therefore, the field populations F4 and S2 were approximately 16- and 26-fold more resistant to clethodim than the susceptible population, SLR4. Also, the S2 population had greater resistance to butroxydim (7-fold) than the F4 population (4.5-fold). Sequencing of the target site of acetyl co-enzyme A carboxylase gene identified two known mutations (aspartate-2078-glycine and cysteine-2088-arginine) in the F4 population and three known mutations (isoleucine-2041-asparagine, aspartate-2078-glycine and cysteine-2088-arginine) in the S2 population. Even though L. rigidum was confirmed resistant to clethodim and butroxydim, use of these (POST) herbicides in combination with preplant incorporated (PPI) herbicides improved weed control and canola yield relative to PPI herbicides only. Atrazine PPI followed by (fb) clethodim + butroxydim POST and atrazine PPI fb atrazine + clethodim POST reduced L. rigidum plant density (∼52%) and seed production relative to the standard grower practice of atrazine PPI fb clethodim POST. These two herbicide combinations produced the highest seed yield of canola (1839–2196 kg ha −1 ). Propyzamide alone (PPI) or as a split application (PPI fb POST) and in a mixture with clethodim improved L. rigidum control (32–63%) as compared to the standard grower practice but had limited impact on L. rigidum seed production. PPI herbicides alone were unable to effectively control clethodim-resistant L. rigidum in triazine-tolerant canola. Highlights: Sequencing of the ACCase gene identified 2041, 2078 and 2088 mutations. Atrazine PPI fb POST clethodim + butroxydim provided highest control of L. rigidum . Propyzamide as PPI or PPI fb POST provided up to 60% control of L. rigidum . No herbicide treatment reduced L. rigidum seed production below 1500 seeds m −2 .